Synthesis of heterobimetallic Zn/Co carbamates: single-source precursors of nanosized magnetic oxides under mild conditions - Domide, Dan; Walter, Olaf; Behrens, Silke; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2011)
Tetrameric Zn alkyl carbamates [ZnR(O2CNR′2)]4 (R = Me or Et, R′ = iPr) have been synthesized from alkylzinc amides and CO2. The reaction of these carbamates with specially designed CoII complexes afforded new heterobimetallic (Zn/Co) carbamate complexes. The thermal decomposition of these single-source precursors under mild conditions (200-300 °C) led to magnetic mixed-metal oxide nanoparticles. Two phases were identified that are isostructural with ZnO (wurtzite phase) and CoO (cubic rock salt structure), but both contain Zn and Co in varying molar ratios. The particles with the ZnO-type structure have a mean average size of 7.7 nm, whereas the particles with the CoO-type structure are much larger (ca. 48 nm).